Nrf2/HO-1 partially regulates cytoprotective effects of carbon monoxide against urban particulate matter-induced inflammatory responses in oral keratinocytes. (September 2020) - Cheng, Ching-Yi; Vo, Thi Thuy Tien; Lin, Wei-Ning; Huang, Hsiang-Wei; Chuang, Chu-Chun; Chu, Pei-Ming; Lee, I-Ta
Graphical abstract: Highlights: PM can cause human oral mucosa inflammation. CORM-2 can inhibit PM-induced inflammatory responses via the Nrf2/HO-1 pathway. CORM-2 can inhibit PM-induced PKCα activation and ROS generation. CORM-2 can inhibit PM-induced NLRP3 inflammasome activation. Abstract: Introduction: Exposure to airborne particulate matter (PM) increases the proportion of oral inflammatory diseases. During the formation of inflammatory conditions, the nucleotide-binding domain and leucine-rich repeat protein 3 (NLRP3) inflammasome activation plays an important regulator. Carbon monoxide (CO) arising from heme degradation, catalyzed particularly by heme oxygenase-1 (HO-1), has been shown to own cytoprotective effects including anti-inflammation and antioxidant. Here, we determined the novel mechanisms of carbon monoxide releasing molecule-2 (CORM-2) on PM-induced inflammatory responses in human oral keratinocytes (HOKs). Methods: The effects of CORM-2 on the expression of various inflammatory proteins induced by PM were determined by Western blot, real-time PCR, promoter assay, and ELISA. The involvement of signaling molecules in these responses was studied by using the selective pharmacological inhibitors and siRNAs. Results: We proved that PM enhanced C-reactive protein (CRP) levels, NLRP3 inflammasome and caspase-1 activation, and IL-1β release, which were reduced by preincubation with CORM-2. Transfection with PKCα siRNA and preincubation with the ROS scavenger (N-acetyl-cysteine, NAC), an inhibitor of NADPH oxidase (diphenyleneiodonium, DPI), or the mitochondria-specific superoxide scavenger (MitoTEMPO) inhibited PM-mediated inflammatory responses. In addition, PM-regulated PKCα and NADPH oxidase activation as well as NADPH oxidase- and mitochondria-derived ROS generation were inhibited by CORM-2, but not inactivate CORM-2 (iCORM-2) pretreatment. At the end, we confirmed that CORM-2 improved PM-induced inflammatory responses via the induction of Nrf2 activation and HO-1 expression. Conclusion: We suggest that CORM-2 inhibits PM-induced inflammatory responses in HOKs via the inhibition of PKCα/ROS/NLRP3 inflammasome activation combined with the induction of Nrf2/HO-1 expression.